Clinical Features, Pathophysiology, and Treatment of Levodopa-Induced Dyskinesias in Parkinson’s Disease - J. Guridi; R. González-Redondo; J. A. Obeso (Parkinson's Disease)
Dyskinetic disorders are characterized by excess of motor activity that may interfere with normal movement control. In patients with Parkinson’s disease, the chronic levodopa treatment induces dyskinetic movements known as levodopa-induced dyskinesias (LID). This paper analyzed the pathophysiology, clinical manifestations, pharmacological treatments, and surgical procedures to treat hyperkinetic disorders. Surgery is currently the only treatment available for Parkinson’s disease that may improve both parkinsonian motor syndrome and LID. However, this paper shows the different mechanisms involved are not well understood.